СЛОЖЕНИТЕ ИМЕНКИ ВО МАКЕДОНСКИТЕ ЦРКОВНОСЛОВЕНСКИ ТЕКСТОВИ: (начинот на поврзување на нивните компоненти) (Filološke pripombe, 2019)
In the old Slavic Macedonian texts the compounds are lexical semantic units formed by amalgamation of two meaningful motivating grounds, and from the whole analyzed material, only three compounds are with three components. Most numerous are the compounds whose components have an interfix. As linking elements occur the vocals –o- or –e-, where the dullness of the interfix –o- is much bigger in comparison with the interfix –e-. The existence of parallel examples of bonding vocals –e- and –o- indicates to generalization of –o- as a bonding vocal. In the old Slavic Macedonian texts the components of the compounds are also without a bounding vocal. The accretions in the texts appear in a limited number, most of which as a first component contain case form, and some of them are formed by direct bonding of the two components. This type of compounds reflect the transitional period of the increase of the dullness of the amalgamation as a model of backformation.